High School Students’ Attitudes and Teachers’ Views Toward English as a Lingua Franca - Sarah Claudia; Ignatius Tri Endarto (English Language in Focus (ELIF), 2023)
English as a lingua franca (ELF) has gained its global significance as the working tongue of the many. This case study was conducted with the aim of investigating students’ attitudes and teachers’ views toward ELF. Through questionnaire and interview, it involved 69 students and 2 English teachers at a senior high school in Indonesia as the participants. Based on the questionnaire results, it was found that the students generally had positive attitudes toward ELF. However, they tended to favor inner-circle Englishes over other varieties. Based on the interview results, the teachers also showed positive views toward ELF. Moreover, they viewed that learning various English varieties was important for the students. They also thought that the use of L1 and L2 in the classroom was needed. Despite their positive views, the teachers were still not really familiar with ELF as a concept and demonstrated different views of native speakerism. In general, there was not much dissimilarity between the high school students’ attitudes and teachers’ views toward ELF. It seems to suggest that the teachers’ views might have played a role in shaping the students’ attitudes toward ELF and, therefore, the students’ attitudes to some degree mirrored the views of their teachers.